2012
DOI: 10.1182/blood.v120.21.1361.1361
|View full text |Cite
|
Sign up to set email alerts
|

Triggering of CD44 by Ultra-Low-Molecular-Weight Hyaluronan Induces Cell Death by Autophagy Via Endoplasmic Reticulum Stress in Acute Lymphoblastic Leukemia with MLL Gene Rearrangements

Abstract: 1361 Acute lymphoblastic leukemia (ALL) with MLL gene rearrangements (MLL+ALL) is chemoresistant and its prognosis is still dismal. MLL+ALL shows a unique gene profile clearly distinguishable from other types of ALL and AML, and CD44 is known as one of specific molecules expressed very highly in MLL+ALL. CD44, a transmembrane glycoprotein recently attracting an attention as a cancer stem cell marker for several types of cancers, is expressed on a variety of cells, and has the specific binding si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…30 Moreover, by triggering CD44, ultralow-molecular-weight HA and MIF were involved in the induction of autophagy in acute lymphoblastic leukemia and endothelial cells, respectively. 28,29 Importantly, our study has unveiled CD44 as a signaling receptor engaged by a matrixderived DAMP to activate autophagy in immune cells.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…30 Moreover, by triggering CD44, ultralow-molecular-weight HA and MIF were involved in the induction of autophagy in acute lymphoblastic leukemia and endothelial cells, respectively. 28,29 Importantly, our study has unveiled CD44 as a signaling receptor engaged by a matrixderived DAMP to activate autophagy in immune cells.…”
Section: Discussionmentioning
confidence: 90%
“…CD44 was attracting attention as a signaling receptor upstream of the autophagic pathway in nonimmune cells. [28][29][30] In vascular smooth muscle cells, the CD44-integrin complex was shown to mediate osteopontininduced autophagy. 30 Moreover, by triggering CD44, ultralow-molecular-weight HA and MIF were involved in the induction of autophagy in acute lymphoblastic leukemia and endothelial cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) [21]. These effects are solely biglycan dependent and independent of HA, osteopontin, and MIF-2 [21,[61][62][63]. Importantly, biglycan-triggered macrophage autophagy does not involve CD14 both in vitro and in vivo [21].…”
Section: Biglycan Triggers Macrophage Autophagy Via Tlr4 and Cd44 Cormentioning
confidence: 94%
“…HA regulates the expression of inflammatory genes in a manner dependent on HA molecular weight, as evidenced by a growing number of reports [6], and several studies have indicated its close involvement in inflammatory arthritis development [7, 8]. High molecular weight (HMW) HA, produced by hyaluronan synthase 1 (HAS1) and HAS2, exerts anti-angiogenic, immunosuppressive, and anti-inflammatory properties [9, 10], whereas low-molecular-weight (LMW) HA, which is synthesized by HAS3, is usually secreted from cells both under physiological and pathological conditions [11]. This LMW-HA functions oppositely to HMW-HA, exerting proinflammatory, angiogenic, and immunostimulatory roles [12].…”
Section: Introductionmentioning
confidence: 99%